High Conductivity and Durability Textile Gas Sensor-Based Polyaniline-Decorated-Poly(3,4-ethylenedioxythiophene)/Poly(4-styrenesulfonate) for Ammonia Detection - Pattanarat K. (2023)
Securing the stability of sensing responses under stretching and washing is essential for textile-based wearable gas sensors. Herein, we report textile-based gas sensors composed of polyaniline (PANi)-decorated poly(3,4-ethylenedioxythiophene)/poly(4-styrenesulfonate) (PEDOT/PSS) coated on cotton yarn. Without conventional hydrochloric acid (HCl) doping, the PANi/PEDOT/PSS sensor exhibits a high electrical conductivity of 1343 S cm-1, good sensitivity, and excellent stability for detecting ammonia, obviously better than the PEDOT/PSS and PANi/HCl sensors. The ammonia sensing response of the PANi/PEDOT/PSS sensor was 7.54% (at 50 ppm), with a detection limit as low as 5 ppm. The enhanced sensing performance is attributed to the heterostructure of PANi and PEDOT/PSS films and the protonation/deprotonation nature of PANi. It was found that the sensing performance of the PANi/PEDOT/PSS sensor is humidity independent. More importantly, the sensor conductivity and sensing response have shown excellent stability under 1100 stretching/releasing cycles and high durability after 10 washing cycles. The results indicate a potential application of wearable textile sensors for detecting ammonia in an environment.